As abordagens tipológicas dos textos - Sousa, Socorro Cláudia Tavares de (2012)
As a part in the area of Text Linguistics, this paper aims to discuss the notion of "textual type" and "textual sequence" within the theoretical framework developed by Koch and Fávero (1987) and by Adam (1992, 2008). To reach such a purpose, we initially discussed the concept of typology, then we investigated the various terminologies and conceptualizations used to frame the “theoretical schemes”, and finally we examined how the notions of "textual type" and "textual sequence" are presented within the typologies selected. The analysis permitted us to observe: convergent aspects regarding the cognitive nature of the concepts and the existence of a limited amount of "text types"; and divergent aspects regarding the relation of influence of the social factors on the concepts analyzed and non-coincidence of types presented.